2022
DOI: 10.1038/s41598-022-22261-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of negative pressures on the superconductivity of amorphous and crystalline bismuth

Abstract: Materials may behave in non-expected ways when subject to unexpected conditions. For example, when Bi was turned into an amorphous phase (a-Bi) unexpectedly it became a superconductor at temperatures below 10 K. Using the superconductivity of the amorphous phase we provided an explanation as to why crystalline bismuth (c-Bi) had not been found to superconduct, and even predicted an upper limit for its superconducting transition temperature Tc. This was experimentally corroborated within the following year. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…154 Pressure changes are often easier to achieve than ultracold temperatures, so room-temperature superconducting materials are expected. Quiroga et al 155 found that their superconducting transition temperature could be increased by expansion. The expansion can be obtained in the lab by chemically etching a double-base alloy because chemically removing an atomic species decreases the density of the material, thereby creating an atomic expansion of the sample.…”
Section: Roboticsmentioning
confidence: 99%
“…154 Pressure changes are often easier to achieve than ultracold temperatures, so room-temperature superconducting materials are expected. Quiroga et al 155 found that their superconducting transition temperature could be increased by expansion. The expansion can be obtained in the lab by chemically etching a double-base alloy because chemically removing an atomic species decreases the density of the material, thereby creating an atomic expansion of the sample.…”
Section: Roboticsmentioning
confidence: 99%